Quelques reflexions sur la variation linguistique - Deshaies, Denise ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1987)
Various social, psychological, and linguistic explanations for language variation are examined from the perspective of a fundamental principle that seems to underline interaction, language, and society. That principle lies in the paradigm "same and different." The dialectic resulting from this paradigm is at the basis of the notions of interaction, language, group, or society. Different social analyses, such as those of status, solidarity, or social class as opposed to social network, fit into the more general principle characterized by the tension between same and different. Based on this perspective, it is proposed that our concepts of language and language teaching must change to accommodate individual perceptions of what is important. (An English abstract accompanies the document.) (Author/MSE)
ERIC Note: In: Blanc, Michel, Ed.; Hamers, Josiane F., Ed. Theoretical and Methodological Issues in the Study of Languages/Dialects in Contact at Macro- and Micro-Logical Levels of Analysis; see FL 016 743.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Interaction; Intergroup Relations; Interpersonal Relationship; Language Research; Language Variation; Linguistic Theory; Second Language Instruction; Social Indicators; Social Structure; Sociocultural Patterns; Socioeconomic Background; Sociolinguistics; Information Analyses; Reports, Evaluative; Speeches/Meeting Papers